Late Stent Thrombosis in a Patient of Clopidogrel Resistance: A Case Report (Ibrahim Cardiac Medical Journal, 2012)
Late stent thrombosis (LST) following drug-eluting stent (DES) implantation is a rare but very fatal complication after percutaneous coronary intervention (PCI). We report a case of LST presenting as non ST elevation myocardial infarction (NSTEMI) at 11 months after deployment of DES. The patient, initially managed with conventional dual-antiplatelet therapy (aspirin and clopidogrel) showed resistance to Clopidogrel on Verify Now P2Y12 assay, and was subsequently substituted with prasugrel.Ibrahim Cardiac Med J 2012; 2(2): 45-49